Seven Andean notes to think Ethics - Mujica Bermúdez, Luis (2017)
The article proposes seven annotations that come from Andean conceptions and practices, which seek to contribute to the reflection on the meaning that ethics has in these times, taking into account the current Quechua language. In this perspective, the article proposes that ethics (yachakuy) is a permanent reflexive practice that is inserted in the current Andean history, where people live with nature and make history to the extent that it considers mutual care and human responsibility as indispensable for a coexistence and true peace.